2003
DOI: 10.1016/s0213-9111(03)71746-4
|View full text |Cite
|
Sign up to set email alerts
|

Violencia del compañero íntimo en España

Abstract: IPV is an increasing public health problem in Spain. There seems to be a bimodal curve by age in mortality from IPV, but no geographical patterns in mortality and the incidence of formal complaints of IPV or between the provinces with the highest incidence of formal complains and those with highest mortality were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 13 publications
1
2
0
3
Order By: Relevance
“…The prevalence in this study did not coincide with the prevalence of reported genderbased violence according to the Ministry of Health, specifically the State Observatory on Violence against Women (10) . Thus, there seems to be a mismatch between the prevalence of violence and reported cases, in accordance with other studies conducted in Spain (21) . The prevalence obtained was similar to that of other studies conducted with health professionals in other countries: a study in Jordan found that 59% of the nurses had suffered psychological IPV (6) ; a study in the United States found that 25% of the nurses had suffered IPV (4) .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence in this study did not coincide with the prevalence of reported genderbased violence according to the Ministry of Health, specifically the State Observatory on Violence against Women (10) . Thus, there seems to be a mismatch between the prevalence of violence and reported cases, in accordance with other studies conducted in Spain (21) . The prevalence obtained was similar to that of other studies conducted with health professionals in other countries: a study in Jordan found that 59% of the nurses had suffered psychological IPV (6) ; a study in the United States found that 25% of the nurses had suffered IPV (4) .…”
Section: Discussionsupporting
confidence: 88%
“…This refers to the fact that the cases of VAW that are filed and those collected through investigations are only a part of the whole, and they are generally the more severe ones. The existence of other forms of violence remains hidden [38]. However, some interviewees consider this invisibility, in the case of Roma women, to be – to a certain point – understandable, without which VAW could become an anti-Roma tool [27].…”
Section: Discussionmentioning
confidence: 99%
“…Por último, se han calculado las tasas de mortalidad brutas por violencia contra las mujeres siguiendo el mismo método aplicado en estudios anteriores 16 . La información se tomó del registro de la Federación de Mujeres Separadas y Divorciadas 17 , y se recogieron desde enero de 1997 a diciembre de 2003.…”
Section: Métodosunclassified